Populations of Saccharomyces cerevisiae in Vineyards: Biodiversity and Persistence Associated with Terroir - González, Magalí Lucía (2023)
The origin terroir provides distinctive characteristics for wines, in relation to soil, climate, oenological practices, etc. Hence, the characterization of each wine region by multiple aspects wouldallow differentiation of its wines. Several approaches at different scales have studied terroir microbiological fingerprints: from global microbiome analysis up to intraspecific Saccharomyces biodiversity. Mature grapes are the primary source of yeasts, and S. cerevisiae is a key wine fermentative species. Malbec is the emblematic Argentinean variety and is mainly cultivated in the “Zona Alta del Rio Mendoza” (ZARM). In this work, the diversity of S. cerevisiae grape populations was studied at three vintages in two Malbec vineyards of the ZARM, to evaluate their annual diversity and behavior in different vintages. Rarefaction of classical ecological indices was applied for a statistically adequate biodiversity analysis. A total of 654 S. cerevisiae isolates were differentiated by Interdelta-PCR. Each yeast grape population showed a unique composition of S. cerevisiae strains; however, a narrow genetic relationship was found in each vineyard. A slight increase in the initial diversity and a stabilization in the diversity of S. cerevisiae populations were confirmed. These results add to the discussion about the contribution of yeasts to the terroir microbiological concept, and its limitations and stability over the time.